Proceeding of the 3rd International Conference on Electronics, Biomedical Engineering, and Health Informatics ICEBEHI 2022, 5-6 October, Surabaya, Indonesia - Triwiyanto, Triwiyanto; Rizal, Achmad; Caesarendra, Wahyu (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book presents high-quality peer-reviewed papers from the International Conference on Electronics, Biomedical Engineering, and Health Informatics (ICEBEHI) 2022 held at Surabaya, Indonesia, virtually. The contents are broadly divided into three parts: (a) Electronics, (b) Biomedical Engineering, and (c) Health Informatics. The major focus is on emerging technologies and their applications in the domain of biomedical engineering. It includes papers based on original theoretical, practical, and experimental simulations, development, applications, measurements, and testing. Featuring the latest advances in the field of biomedical engineering applications, this book serves as a definitive reference resource for researchers, professors, and practitioners interested in exploring advanced techniques in the fields of electronics, biomedical engineering, and health informatics. The applications and solutions discussed here provide excellent reference material for future product development.
A Preliminary Study of Vehicle License Plate Detection and Identification -- Feature Selection using Extra Trees Classifier for Research Productivity Framework in Indonesia -- A Survey on Big Data Analytics for Load Prediction in Smart Grids -- Analysis of Three Phase Induction Motor Speed Performance with Load Torque Changes Using Inverter Space Vector Pulse Width Modulation (SVPWM) Control -- Assessing the Effect on Cognitive Workload Index, EEG Band Ratio's, Band Frequencies Using Band Power and Implementing Machine Learning Classification -- Fetal ECG Signal Processing Using One-Dimensional Convolutional Neural Network (1-D CNN) for Fetal Arrhythmias Detection -- Diabetic Retinopathy Classification based on Fundus Image using Convolutional Neural Network (CNN) With MobilenetV2 -- Image Improvement and Dose Reduction on Computed Tommography Mastoid Using Interactive Reconstruction -- Classification of Pneumonia Based on X-Ray Images with ResNet-50 Architecture -- A Model Convolutional Neural Network for Early Detection of Chili Plant Diseases in Small Datasets -- Early Risk Pregnancy Prediction Based on Machine Learning Built on Intelligent Application using Primary Health Care Cohort Data.
Keywords: Electronics; Biomedical engineering; Medical informatics; Electronics and Microelectronics, Instrumentation; Biomedical Engineering and Bioengineering; Health Informatics